Mekanisme Sistem Pengelolaan Sampah Kapal di MT. Petromax dalam Upaya Menjaga Kelestarian Lingkungan Laut - Saraswati, Indah; Heriawan, Mohammad Sapta; Rediyanto, Rediyanto (Politeknik Ilmu Pelayaran Semarang, 2025)
Shipping activities are one of the causes of marine pollution. The frequent occurrence of pollution in the sea by garbage from ships requires prevention and control efforts. This is what was done by MT. Petromax as a commercial ship operated to transport Crude oil cargo both domestically and abroad. This research aims to examine the implementation of the ship garbage management system mechanism on MT. Petromax in an effort to preserve the maritime environment. The method used is descriptive qualitative with observation and document study approaches. The results showed the efforts of MT. Petromax in preventing and overcoming the pollution of marine debris with the Garbage Management Plan. Garbage management carried out by MT. Petromax is processing garbage through two efforts i.e. 1) garbage management with incinerators, 2) management handling garbage on board and 3) garbage management with Garbage Boat for disposal garbage to receiption shore facility.